Modern contraceptive methods utilization and associated factors among reproductive aged women in rural Dembia District, northwest Ethiopia: Community based cross-sectional study - Shibihon Debebe; Miteku Andualem Limenih; Belete Biadgo (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Improving women’s health through modern contraceptive methods utilization is the key strategy to prevent unwanted pregnancy and its complication. However, there was limited evidence on utilization of modern contraceptive methods in the study area. Objective: This study identified factors affecting utilization of modern contraceptive methods among women at reproductive age group in rural areas of Dembia district, 2015. Materials and Methods: Community based cross sectional study was conducted in 2015 in Dembia District. Multi-stage sampling technique was used to select a total of 616 study participants. Bivariate and multivariable logistic regression model was fitted to identify factors associated with modern contraceptive utilization. Odds ratio with 95% confidence interval (CI) was computed to determine the level of significance. Results: Modern contraceptive methods utilization was found to be 31.7% 95%CI (28.0-35.3). Age [Adjusted odds ratio (AOR): 1.94, (95%CI: 1.170-3.216)], women who has educated husband [AOR: 0.28, (95%CI: 0.117-0.666)], Marital status [AOR: 2.81, (95%CI: 1.344-5.855)] and Spousal announcement about family planning issues [AOR: 2.58, (95%CI: (1.276-5.202)] were factors associated with modern contraceptive methods utilization. Conclusion: Modern contraceptive methods utilization was found to be low. Providing educational opportunities, creating awareness about contraception and effective counseling would increase modern contraceptive methods utilization